Estudos métricos da informaçao em periódicos do Portal SciELO: visibilidade e impacto na Scopus e Web of Science - Lazzarotto Freitas, Juliana (2017)
This study aims to analyze the visibility of the journals that publish research on metric studies (MS) by using the impact indicators of these journals, present at the databases Scopus and Web of Science (WOS). The selected journals represent the domain metric studies in the SciELO database and are present in the other databases, which were taken from their citation indicators. The study identifies the total number of each journal and the total number of publications related to metric studies in the 2009-2013 period, and the total number of citations received by each journal and his quote to MS articles in the time window 2009-2016, showing the average quotation by journal, areas and countries in the thematic and in their general publication. Soon after, it compares the citation measures given by the SJR of Scopus and the JCR Web of Science, pointing journals, areas and countries with the greatest impact on the theme and overall. It concludes that the majority of the journals have a higher number of citations in Scopus over the WOS, suggesting greater visibility in the first database to the articles about with metric studies. A similar situation occurs when considering any scientific journal and their citations received in relation to their overall impact. In relative terms, it observes that, in both databases, the Applied Social Sciences journals presents the highest percentage of articles on EMI in detriment to the other disciplines journals. Finally, it considers that Scopus indexing policies are responsible for their wider coverage and greater visibility of their journals, which are available in different languages